Using the Turkish Red Pine Tree to Monitor Heavy Metal Pollution - YARCI, CELAL; ÖZYİĞİT, İBRAHİM İLKER (HARD, 2020)
Turkish red pine is an evergreen tree species widely distributed in the Aegean and Mediterranean regions in Turkey. In the present work, the heavy metal pollution level in Istanbul was investigated using Turkish red pine as a biomonitor. For determining heavy metal concentrations (Cd, Co, Cr, Mn, Ni and Pb) in leaf (unwashed and washed) and bark samples of Turkish red pine and its co-located soil samples we used ICP-OES. Additionally, particulate matter profiles of the research areas were investigated. The samples were collected from 5 different localities: 4 from the Bosporus region (Yildiz Grove, Fethi Pasha Grove, Baltalimani Grove and Mihrabad Grove) and one from Prince Island, also known as Buyukada (as control). According to our measurements, the highest heavy metal accumulations (in mg kg(-1) DW) in plant part samples were measured between 1.526 +/- 0.012 and 1.639 +/- 0.015 for Cd, 0.543 +/- 0.007 and 0.600 +/- 0.009 for Co, 5.110 +/- 0.064 and 5.648 +/- 0.072 for Cr, 9.347 +/- 0.105 and 10.331 +/- 0.111 for Mn, 7.483 +/- 0.091 and 8.271 +/- 0.096 for Ni, and 13.848 +/- 0.159 and 14.950 +/- 0.167 for Pb, while the highest heavy metal accumulations (in mg kg(-1) DW) in soil samples were measured between 1.813 +/- 0.021 and 1.974 +/- 0.029 for Cd, 6.326 +/- 0.082 and 6.992 +/- 0.091 for Co, 22.017 +/- 0.284 and 23.685 +/- 0.301 for Cr, 268.333 +/- 3.153 and 297.361 +/- 3.529 for Mn, 15.194 +/- 0.176 and 16.792 +/- 0.193 for Ni, and 68.778 +/- 0.715 and 74.514 +/- 0.883 for Pb. The highest outdoor particulate matter levels (in mu g/m(3)) in research areas were also determined as 27.103 for fine (PM2.5) and 67.792 for coarse (PM10) aerosols. The findings revealed that Turkish red pine could accumulate noteworthy amounts of heavy metals.
Keywords: heavy metals; particulate matter (PM); Pinus brutia; contamination; TRACE-ELEMENTS; LEAD PB; BIOMONITOR; BARK; L.; BIOINDICATOR; ACCUMULATION; REGION; CITY